2023
DOI: 10.1136/bmjmed-2022-000468
|View full text |Cite
|
Sign up to set email alerts
|

T cell immune memory after covid-19 and vaccination

Lulu Wang,
Alex Nicols,
Lance Turtle
et al.

Abstract: The T cell memory response is a crucial component of adaptive immunity responsible for limiting or preventing viral reinfection. T cell memory after infection with the SARS-CoV-2 virus or vaccination is broad, and spans multiple viral proteins and epitopes, about 20 in each individual. So far the T cell memory response is long lasting and provides a high level of cross reactivity and hence resistance to viral escape by variants of the SARS-CoV-2 virus, such as the omicron variant. All current vaccine regimens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 147 publications
0
5
0
Order By: Relevance
“…Although cell-mediated immunity can ensure rapid clearance of the virus, possibly reducing the clinical significance and duration of the disease, it may not offer a complete protection from infection. Moreover, the evaluation of virus specific cell-mediated immunity and correlates of protection are more technically complicated and resource-demanding compared to the assessment of the humoral immunity [38].…”
Section: Discussionmentioning
confidence: 99%
“…Although cell-mediated immunity can ensure rapid clearance of the virus, possibly reducing the clinical significance and duration of the disease, it may not offer a complete protection from infection. Moreover, the evaluation of virus specific cell-mediated immunity and correlates of protection are more technically complicated and resource-demanding compared to the assessment of the humoral immunity [38].…”
Section: Discussionmentioning
confidence: 99%
“…While T-cells induced by mRNA COVID-19 vaccination exclusively target the protein S, SARS-CoV-2 natural infection elicits a T-cell response against a wider breadth of antigens (structural and nonstructural proteins) derived from the entire viral genome [2,41]. Therefore, the higher Positivity Rate of QFN-SARS-CoV-2 Extended Pack and possibly Ag3 may be attributed to the misclassi cation of some participants as COVID-19-naïve as we cannot rule out the possibility that some participants might have had asymptomatic or seronegative SARS-CoV-2 infection [42].…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been discussed that heterogeneous immune imprinting repertoires would depend on several factors, including whether the population was vaccinated before infection, the type of vaccine, the infectious strain, and the particular conditions of the host ( 235 , 236 ). Despite the above, epidemiological studies have shown that antibody levels gradually decrease over time, so they do not offer long-lasting protection against SARS-CoV-2 infection ( 233 , 237 ). Moreover, considering the above, the emergence of viral variants with a repertoire of mutations in the Spike protein and the receptor binding domain (RBD) allows the virus to evade the binding and neutralization of antibodies, leading to outbreaks of reinfection around the world ( 237 ).…”
Section: Sars-cov-2 Infection Onset Progression and Pathophysiology O...mentioning
confidence: 99%
“…Similar results have been described for inactivated vaccines, which induce T cells responses against epitopes of the Spike proteins, as well as other SARS-CoV-2 proteins included in the inactivated viral particle, both in adults and children (227)(228)(229)(230)(231). Particularly, the consequent T cell response against the Omicron variant persisted after 6 months: 84% for CD4 +T cells and 85% for CD8+ T cells, determined by activationinduced markers (232)(233)(234). Consistently, activation of specific CD4+ T cells was detected in individuals vaccinated with Coronavac ® for 4 weeks after the second booster, and these cells demonstrated to be responsive against the SARS-CoV-2 Wild type and Omicron variants.…”
Section: Viral Evasion and Immune Response To Sars-cov-2 Infectionmentioning
confidence: 99%
See 1 more Smart Citation